2020
DOI: 10.1016/j.ekir.2019.12.012
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Acute Effects of Hemodialysis on Skeletal Muscle Perfusion, Metabolism, and Function

Abstract: Introduction:The underlying mechanisms of skeletal muscle wasting in hemodialysis patients are complex. We performed a systematic review to summarize evidence on whether hemodialysis has acute effects on skeletal muscle perfusion, metabolism, and function. Methods:The protocol was registered on PROSPERO (Registration number CRD42018103682). A systematic search was performed in MEDLINE, PubMed, Cochrane, Embase, Scopus, and Web of Science. Citation, reference list, and gray literature searches were also perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Another protein that is inhibited by HMB is caspase 3 ( CASP3 ) [ 10 ]. This protein has not only a positive effect on DMD [ 63 ] but also enhances some biological processes such as apoptosis and protein degradation [ 63 , 64 , 65 ] ( Figure 3 ).…”
Section: Common Pathwaysmentioning
confidence: 99%
“…Another protein that is inhibited by HMB is caspase 3 ( CASP3 ) [ 10 ]. This protein has not only a positive effect on DMD [ 63 ] but also enhances some biological processes such as apoptosis and protein degradation [ 63 , 64 , 65 ] ( Figure 3 ).…”
Section: Common Pathwaysmentioning
confidence: 99%
“…On one hand, acute studies assessing muscle and whole body protein turnover conducted in stable patients have consistently demonstrated an imbalance in protein synthesis and degradation during HD sessions[ 105 - 108 ]. It has been also shown that losses of amino acids during HD, ranging between 8 and 10 g per session, contributed significantly to the net protein catabolism[ 85 , 109 - 111 ].…”
Section: Intermittent Extracorporeal Renal Replacement Therapy Is The...mentioning
confidence: 99%
“…Monitoring training is becoming indispensable to fine-tune the dose-response and, ultimately, improving performance. Muscle oxygen saturation (SmO 2 ) has been gaining emphasis as a local muscle measurement at rest and during exercise [ 12 ], not only in terms of sports performance [ 13 ] but also in terms of health [ 14 , 15 ]. Near-infrared spectroscopy (NIRS) is a non-invasive method that continuously monitors information about the changes in oxygenation and haemodynamics in muscle tissue [ 16 ].…”
Section: Introductionmentioning
confidence: 99%